Effects of Fast Food Consumption on Adolescent Health: A Literature Review - Kurniawan, Muhammad Yahya Nuzulul; Anggriyani , Farida Catur Wahyu (Tinta Emas Institute, 2024)
Ready-to-eat food is food that can be easily and quickly prepared as a substitute for home-cooked food. The popularity of fast food or fast food among teenagers is increasing, along with the increase in portions and energy contained in it. Several factors that support the consumption of fast food by teenagers include knowledge, peer influence, a comfortable place to gather, good taste, convenience and practicality, pocket money, affordable prices, and fast food brands. This research aims to determine the negative impacts that can be caused by consuming fast food on teenagers. This research was conducted using qualitative analysis methods through literature studies obtained from Google Scholar relating to the influence of fast food consumption among teenagers. Research results show that consumption of fast food by teenagers can cause dangerous diseases such as high cholesterol, diabetes, heart disease, kidney problems and liver damage. Apart from that, excessive consumption of fast food can also increase the risk of obesity in teenagers.